Physicochemical properties govern the activity of potent antiviral flavones - Martin-Benlloch, Xavier; Haid, Sybille; Novodomská, Alexandra; Rominger, Frank; Pietschmann, Thomas; Davioud-Charvet, Elisabeth; Elhabiri, Mourad (ACS omega, 2019)
Ladanein (i.e., 5,6,7-trihydroxylated flavone) was demonstrated to act as a powerful virucidal agent toward a broad range of enveloped virus particles. Fe(III) coordination and pH are indeed among the key parameters that might favor both bioactivation of the flavone and consequent host cell entry inhibition. In this present work, the impact of fluorinated groups on the physicochemical and antiviral properties of the flavone was investigated, thus allowing a deeper understanding of the antiviral mode of action. The improved synthesis of ladanein allowed accessing a broad range of analogues, some of them being significantly more active than the former ladanein lead compound. We first determined the acido-basic properties of this homogenous series of compounds and then investigated their electrochemical behavior. Fe(III) coordination properties (stability, spectral behavior, and kinetics) of ladanein and its analogues were then examined (quasiphysiological conditions) and provided key information of their stability and reactivity. Using the determined physicochemical parameters, the critical impact of the iron complexation and medium acidity was confirmed on hepatitis C virus (HCV) particles (pre)treated with ladanein. Finally, a preliminary structure-HCV entry inhibition relationship study evidenced the superior antiviral activity of the ladanein analogues bearing an electron-withdrawing group in para position (FCF3 > FOCF3 > FFCF3 > FF > FOMe) on the B cycle in comparison with the parent ladanein itself.
Gesehen am 24.07.2019